Effect of cylic stress range on crack growth of aluminium alloy under axial loading - Mohamad Shaffawi, Zainon (2010)
This thesis presented about the fatigue life of the material, which is focus on aluminium alloy. There are some important analysis needs to be done including stress analysis, and also fatigue analysis. People might prefer predict the fatigue life of aluminium alloy using experimental approach. But in this thesis, it comes out with different ways, by using software. The software used is MSC PATRAN with MSC NASTRAN as a solver and MSC Fatigue. The model is developed using the SOLIDWORKS. The results from initial analysis will be proceeding with second analysis which is fatigue simulation. Finally, the crack growth graph will be constructed. The effect of stress ranges of aluminium alloys on fatigue crack growth rate was simulated using the Compact Tension specimen as a model. The Fatigue Crack Growth curve, da/dn as a function of stress intensity factor, ΔK was plotted in order to analyze the crack growth properties of aluminium alloys. It has been done using MSC FATIGUE software. 4 different stress ranges were selected in range (4-10) kN in order to investigate the effect of stress range on crack growth rates. The model were simulated by means of Mode I loading in constant temperature and frequency. The constant value of C and gradient, m according to Modified Paris Law equation, are 1.2E-10 and 4.06 respectively. The life cycle graph (S-N curve) of aluminium alloy under this simulation will be compared to the established life cycle graph. It was show that the aluminium alloys have endurance limit of 95MPa.